2006
DOI: 10.1271/bbb.70.881
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Study on αGln90 of Fe-Type Nitrile Hydratase fromRhodococcussp. N771

Abstract: Nitrile hydratase (NHase) from Rhodococcus sp. N771 is a non-heme iron enzyme having post-translationally modified cysteine ligands, alphaCys112-SO2H and alphaCys114-SOH. We replaced alphaGln90, which is conserved in all known NHases and involved in the hydrogen-bond network around the catalytic center, with glutamic acid or asparagine. The kcat of alphaQ90E and alphaQ90N mutants decreased to 24% and 5% that of wild type respectively, but the effect of mutations on Km was not very significant. In both mutants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 1 publication
2
28
1
Order By: Relevance
“…In the crystal structure of inactive NHase, several functionally important hydrogen bonds were observed in the catalytic center (14,15,76,78). We were able to identify the same interactions in our models and to check their role in the enzyme dynamics.…”
Section: Functional Hydrogen Bondsmentioning
confidence: 76%
“…In the crystal structure of inactive NHase, several functionally important hydrogen bonds were observed in the catalytic center (14,15,76,78). We were able to identify the same interactions in our models and to check their role in the enzyme dynamics.…”
Section: Functional Hydrogen Bondsmentioning
confidence: 76%
“…The protein in these assays underwent lyophilization to remove natural abundance water and was also incubated for at least an hour after being resuspended in the labeled [ 18 O]water before being added to substrate. Studies using 17 O-labeled water and electron paramagnetic spectroscopy have shown that water molecules in the active site, specifically the active site metal-bound aquo or hydroxo ligand, are easily exchangeable (24,25). Additionally, the active sites of NHases exist at the interface of the ␣-and ␤-subunits (26,27), and because ToyJ in this experiment is monomeric (16), the active site is unlikely to harbor tightly nonexchangeable water molecules as it is probably exposed to the solvent.…”
Section: Figure 2 Analysis Of Toyj Mass Spectrometry Data For Incorpmentioning
confidence: 83%
“…1C predicts that solvent-derived oxygen would be incorporated on the first and all subsequent turnovers and that the protein would never become enriched with solvent-derived oxygen. Single turnover experiments to distinguish between these possibilities are challenging because of the relatively high catalytic efficiency of this class of enzyme with turnover rates for aromatic nitrile substrates ranging from 90 to 159 s Ϫ1 and turnover rates for aliphatic nitrile substrates approaching 1,000 s Ϫ1 and even 4,500 s Ϫ1 for a thermophilic NHase (15)(16)(17)(18).…”
Section: Nitrile Hydratases (Nhases)mentioning
confidence: 99%
“…However, αGln90 is conserved in all known NHases and involved in the hydrogen‐bonding network around the catalytic center. The mutation of this residue resulted in a decrease of the enzymatic activity . Furthermore, βArg52 plays an important role in α subunit exchange and may have a positive effect on the catalytic efficiency .…”
Section: Resultsmentioning
confidence: 99%